Design of nonlinear-Lamb-wave-based structural health monitoring systems with mitigated adhesive nonlinearity. (4th September 2018) - Shan, Shengbo; Cheng, Li; Wen, Fuzhen
Abstract: Structural health monitoring (SHM) techniques with nonlinear Lamb waves offer the possibility of detecting incipient damages through the second harmonic generation. Particularly, the primary S0-secondary S0 Lamb wave mode pair in a weakly nonlinear plate is promising for SHM due to its appealing characteristics such as the cumulative second harmonic generation and flexible frequency selection. In a practical PZT-actuated SHM system, apart from the damage-related material nonlinearity of the plate (MNP), the adhesive nonlinearity (AN) is also proven to be a non-negligible nonlinear source, which may jeopardize damage diagnosis if not properly apprehended. By combining a nonlinear shear-lag model and the normal mode expansion method, a theoretical model is proposed in this work, which allows the investigation and the comparison of these two types of important nonlinearities in the system (AN and MNP). With the developed model, optimized nonlinear Lamb wave-based SHM systems can be designed with the mitigated influence of the undesired AN on the system. Finite element (FE) simulations are carried out to validate the proposed model and the effectiveness of the optimized systems through a tactical adjustment of the different nonlinear sources. The designed optimized system is verified by experiments, in comparison with an arbitrarily chosen one. The dominance level of the nonlinear sources in the two systems is evaluated through changing the MNP, which is realized by a thermal aging treatment. Both FE and experimental results demonstrate that the proposed model can effectively guide the design of SHM systems to mitigate AN so that the MNP can be well measured and further used as an indicator of the incipient structural damage.